Role Stakeholders in Forest Managemen And Natural Tourism of Mapilli Forest Managemen Unit in Polewali Mandar District - Muhammad Sarif; Widyanti Utami A; Yulsan Demma Semu (Jurnal Penelitian Kehutanan BONITA, 2023)
Forests are natural resources that have various important functions both ecologically and economically. This study aims to formulate a strategy for forest management and natural tourism that is appropriate to improve the welfare of the community around the forest area. This research was conducted at Mapilli KPH, Polewali Mandar Regency, West Sulawesi Province. Data collection uses in-depth interview techniques. Data analysis was carried out descriptively using the theory of stakeholders analysis Reed et al. 2009. The results showed that there were ten stakeholders in forest management and tourism in Mapilli KPH, each of which had its own role and interests. Based on the assessment of the interests and strength of stakeholders in forest and tourism management classified as not yet effective.